Establishing a baseline of interprofessional education perceptions in first year health science students. - Huebner, Sydney; Tang, Qianxi (Chancy); Moisey, Lesley; Shevchuk, Yvonne; Mansell, Holly (Journal of Interprofessional Care)
Interprofessional education (IPE) is increasingly utilized to prepare students for their future careers in the health sciences as collaborative practitioners. Although it is considered an accreditation requirement in most health science disciplines, little is known about first year student's perceptions of IPE in Canada. In September of 2018, students from dentistry, kinesiology, medicine, nursing, nutrition, pharmacy, and physiotherapy in their first year of their professional program at the University of Saskatchewan were surveyed to obtain a baseline of perspectives and attitudes toward IPE. The survey consisted of an adaptation of the Readiness for Interprofessional Learning Scale (RIPLS) and additional questions to assess students' skills and interest in IPE. Descriptive and univariate statistics were used to determine associations with demographic variables. The response rate was 88% (n= 509). Health science students in all disciplines had positive perceptions of IPE, with overall mean RIPLS scores for domain 1 (teamwork and collaboration), 2 (professional identity), and 3 (roles and responsibilities) of 40.5/45, 33.3/40 and 6.3/10, respectively. Students in kinesiology had significantly lower RIPLS scores than other health science disciplines (p<.05). Female gender, and having a past degree, or previous experience with interprofessional collaboration through school or work were traits that were associated with statistically significantly higher RIPLS scores (p<.05).